Schooling for social transformation? A mixed methods social network case study of a school and its collective music education programme - Sarazin, M (2018)
Schools have often been depicted as instruments of social reproduction. However, they have also long been imbued with the hope that, if harnessed properly, their social dynamics could enable students to change their social positions and acquire the dispositions necessary to change society for the better. Lately, advocates of group music-making have also started claiming that music has a ‘power’ that gives it the capacity to transform both individuals and communities. Yet, little is known about how educational practices in either schools or music programmes shape the relationships between individuals which underpin social transformation processes. This thesis responds to this gap in knowledge. In it, I study a case of a combined day and boarding school which targeted students with schooling difficulties and sought to achieve social transformation goals. The school implemented a collective music education programme to help achieve its aims, making it ideal for studying how educational practices in schools and music programmes impact on students’ relationships and relate to social transformation. I carried out a Mixed Methods Social Network Analysis investigation of the case during one school year. This involved ethnographic fieldwork throughout, as well as two waves of questionnaires and social network measurements. After describing the school’s mission and its key educational practices, I set out their consequences for students’ social lives. I argue that the school’s practices of using social dynamics in school groups (school classes, boarding houses…) to achieve social transformation contributed to the establishment of what I call ‘collectivity’ and ‘intensity’. ’Collectivity’ meant that friendship relations were concentrated within school groups, while ‘intensity’ encouraged student performances and resulted in students’ attentions being turned towards school events. I explore how these paradigmatic notions led to concentrations of not only friendship but also disliking ties in the school. Subsequently, I show how related educational practices made older students and boys more influential, and thus inordinate recipients of positive and negative sentiment ties in the school. The second half of the thesis turns to the music programme, looking at how and for whom it was able to achieve its transformational goals. I first examine the role of performances in the programme. I find that, in order to promote social cohesion and encourage students to appropriate the programme for their self-realisation, music teachers needed to provide students with valued opportunities to perform. I go on to enquire whether the music programme, in introducing a novel domain of musical competence, provided students who were otherwise marginal with a new resource to become influential in the school’s social world. I reveal that students who were already influential before the programme started, namely due to their age, gender, and friendship ties, tended to become musically influential among their peers. The thesis concludes that the school’s educational practices aimed at achieving social transformation not only powerfully influenced students’ relationships but also ultimately limited the school’s ability to attain its transformational goals. They did this by fostering antipathy and unequally distributing resources for students to improve their social positions. Meanwhile, the music programme ended up being so significantly shaped by the school context that its transformative potential was also bounded by the school’s social dynamics. The final chapter of the thesis considers the limitations of my findings, discusses their implications for scholars and practitioners interested in schools, music programmes, and social networks, and offers some reflections on the processes underlying them.